Teaching and Learning Transactional Dialogue through Flipped Classroom for Millennial Students in Urban era - Rachmatillah, Intan; Munir, Ahmad; Anam, Syafiul (VELES Voices of English Language Education Society, 2019)
The aim of this research is knowing is the implementation of a Flipped classroom during the process of learning English in expressing transactional dialogue towards millennial students nowadays. Because flipped classroom creates a different atmosphere since it relates to technological activities. In this research, the researcher tried to include digital videos as a bridge to connect the students? activity in using technology with their English lesson through YouTube as social media. In this research used qualitative research design. It used to know-how is the implementation of the flipped classroom for millennial students. This research contains some students in the tenth grade of science class group and a teacher from one of state senior high schools in Gresik region. In collecting data, the researcher used observation to know what the activities in depth during the implementation of the flipped classroom.